PERAN LEMBAGA PENDIDIKAN DALAM MEMBANGUN BUDAYA MULTIKULTURAL SESUAI DENGAN HUKUM ISLAM - T, Marlini; AM, Rusydi; Saputra, Riki; Wahyuni, Sri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Indonesia as an archipelagic country with thousands of islands, ethnic groups, regional languages, and religions, is a real portrait of a multicultural society. This article discusses the strategic role of educational institutions in building a multicultural culture that is in line with the values ​​of Islamic law. In the context of a pluralistic society, education is the main means to instill the values ​​of tolerance, justice, and mutual respect between ethnic, cultural, and religious differences. Islamic law, as the normative foundation of Muslims, teaches the principles of peaceful coexistence and upholds humanity. Through an inclusive curriculum, character building, and exemplary behavior from educators, educational institutions can become agents of change in creating social harmony rooted in Islamic teachings. This article uses a qualitative-descriptive approach with an analysis of Islamic literature and education policies in Indonesia. The results of this study illustrate that the integration of multicultural values ​​and Islamic law in a more inclusive education system can strengthen social foundations and minimize the potential for conflict in a plural society.